Improving Students’ Ability in Using English with A Simple Translation: A Case on Elementary School Level - Erika Sinambela; Roswani Siregar; Carolina Pakpahan (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
Although English is now being learned in every stage of education, but students always get problem to learn it. This research study explores the use of simple translation for English language improvement among 3rd-grade students at the elementary school level. Adopting a qualitative approach with a survey method, the study aims to investigate students' perception of simple translation and describe its implementation in the classroom. The findings reveal a positive perception of simple translation, with some students expressing a liking for its effectiveness in enhancing their English language skills. These findings highlight the potential benefits of incorporating simple translation into language learning activities. The study provides insights into the types of activities and the teacher's role in implementing simple translation. These findings contribute to the understanding of language learning strategies for young learners and inform the development of effective pedagogical approaches for English language improvement at the elementary school level.